Presupposisi Tokoh Beik Dalam Novel Himar Hakim - Nurzaqiyah, Zulfa; Akmaliyah, Akmaliyah (Hijai - Journal on Arabic Language and Literature, 2018)
Abstract: Novel Himar Hakim by Taufiq Hakim tells about the friendship that exists between a writer named Beik with a pet donkey, which sometimes Beik equates his habit with the donkey. The novel is very philosophical and full of psychic experiences from the main characters described. The main character of the novel is the Taufiq Hakim, in terms of the background in Egypt, and the professor, a writer who in the novel is portrayed by a film dialog writer. The form of the conversation in the novel Himar Hakim by Taufik Hakim is inseparable from the act of speech or the intent to be conveyed by the author to the reader. In Himar Hakim's novel, there are speeches of Beik figures with various forms and objectives of the act of speech and the type of preoccupation. The problems discussed in this research are: how the act of indirect illustration of Beik in the novel of Judge Himar Hakim by Taufik Hakim, and how the presupposition of Beik speech acts in the novel Himar Hakim by Taufik Hakim. The purpose of this research is to know the act of indirect illusions of Beik in the novel of Himar Hakim by Taufik Hakim, and to know the type of presupposition of Beik's speech acts in the novel Himar Hakim by Taufik Hakim. To achieve these objectives, this research uses descriptive analytic method. Then in the data collection techniques using the method refer, then the data were analyzed by using the method of extralingual padan and grouping Beik's speech by using pragmatic approach of speech acting theory and pre-response. Based on the analysis of the novel Himar Hakim by Taufik Hakim, it can be concluded that in the novel there are speeches that contain representative, directive, expressive, commodative and declarative illustrations, with various purposes, including: affirming, stating, asking , ordering, suggesting, commanding, blaming, denouncing, apologizing, insinuating, complaining, refusing, declaring ability, swearing, offering, promising, expecting, praying, and decisive. Expressive speech acts with the purpose of mocking into the findings that dominate Beik's speech. The types of presuppositions contained in the speech are such as existential prejudice, factual presupposition, lexical presuppositions, non-factual presuppositions, structural presuppositions and counterfactual presuppositions. Factual acceptability became the findings that dominated Beik's speech.